FTIR spectroscopic and multivariate analysis for sample discrimination and adulteration detection of ulin seed (Eusideroxylon zwageri Teijsm. & Binn.) oil - Indah Noor Rahmah Indah; Liling Triyasmono Liling; Normaidah Normaidah; Febyanti Safitri; Hayatun Nisa (Universitas Ahmad Dahlan, 2026)
Ulin seed oil has been empirically used by the people of Kalimantan as a natural hair darkener and hair growth promoter. However, standardized extraction methods and sample characteristics for ulin seed oil (USO) have not yet been clearly established. This study aims to determine the optimal. characteristics of ulin seeds for oil extraction and to identify USO adulteration using FTIR spectrophotometry combined with principal component analysis (PCA). Oil extraction was performed using the Soxhlet method with n-hexane as the solvent, employing variations in seed characteristics. Adulterant oils used to detect the authenticity of USO were candlenut oil (CNO) and virgin coconut oil (VCO). The results showed that the most optimal ulin seeds for oil extraction were fresh, mature, and resinous seeds. Adulteration of USO could be detected at wavenumbers 3008, 1745, and 1118 cm⁻¹. PCA analysis of the FTIR spectral data showed that the wavenumber 1745 cm⁻¹ is a variable that can be used to detect adulteration of USO.